Effect of cariogenic challenge on the stability of dentin bonds - Fernanda Blos BORGES; Ellen Luisa KOCHHANN DE LIMA; Fernanda Wiengartner MACHADO; Noeli BOSCATO; Francoise Helene VAN DE SANDE; Rafael Ratto de MORAES; Maximiliano Sergio CENCI (University of São Paulo, 2014)
Objective: The oral environment is subject to biofilm accumulation and cariogenic challenge, and few studies exist on the effect of these factors on the bond strength of adhesive systems. The aim of this study was to test if the exposure of adhesive interfaces to cariogenic challenge under biofilm accumulation could promote higher degradation than the exposure to biofilm accumulation alone. Material And Methods: Five molars were ground until exposure of medium dentin and then restored (Single Bond 2 and Z250 3M ESPE). The tooth/resin sets were cut to obtain beam-shaped specimens, which were distributed according to the aging conditions (n=20): water for 24 h (control); biofilm under cariogenic challenge for 3, 5 or 10 days; biofilm without cariogenic challenge for 10 days; and water for 3 months. Microcosm biofilms were formed from human saliva and grown in a saliva analogue medium, supplemented or not with sucrose to promote cariogenic challenge. Specimens were tested for microtensile bond strength, and failure modes were classified using light microscopy. Bond strength data were analyzed using ANOVA and failure modes were analyzed using ANOVA on ranks (α=0.05). Results: No significant differences in bond strength were detected among the aging methods (P=0.248). The aging period was associated with an increase in the frequency of adhesive failures for the groups aged for 10 days or longer (P<0.001). Conclusion: Aging leads to a higher prevalence of interfacial adhesive failures, although this effect is not associated with cariogenic challenge or reduction in bond strengths.